Population dynamics of soybean stem fly Melanagromyza sojae (Diptera: Agromyzidae) and its parasitoids in Maharashtra State of India. (16th October 2017) - Fand, Babasaheb B.; Gaikwad, Mahesh B.; Sul, Nitin T.; Kumar, Mahesh; Bhagat, Kiran P.; Bal, Santanu K.; Minhas, P.S.
Abstract: The cryptic nature and lack of consistent biological control of the stem fly, Melanagromyza sojae Zehntner, an emerging pest of soybean, Glycine max (L.) Merrill, necessitated the monitoring and assessment of the impact of the parasitoid complex on seasonal regulation of the pest population. In this paper, we measure and relate, using the host density as a predictor variable, the seasonal density dependence of M. sojae parasitoids and the level of parasitism in soybean fields. The results revealed density dependence of parasitioids. The populations built up concomitant with the host insect, reached their peak during the mid-season, and declined towards the end of the crop season. A complex of 10 species of hymenopteran parasitoids comprising six species from Pteromalidae and one species each from the families Eurytomitidae, Eucoilidae, Braconidae and Eulopidae had a significant impact on M. sojae populations with a peak parasitism of 50%. The seasonality and relative abundance of parasitoids were explored. Eurytoma sp. (Eurytomitidae) and Gronotoma sp. (Eucoilidae) were the most prevalent parasitoids throughout the season, whereas the pteromalid Sphegigaster sp. was dominant during the mid-season. The modulation of management practices aimed at conservation of these bioagents could improve the biological control of M. sojae populations. We discuss the practicality of several management options aimed at achieving this goal.